Nursing care for pregnant women diagnosed with COVID-19 - Monroy Herrera, Ludy Esther; Manrique Peña, Stefany; Pulido Montes, Maria Andreina; Rincón Romero, Katherine (Salud Integral y Comunitaria, 2025)
Introduction: The nursing intervention is fundamental in pregnant women con COVID-19, focusing on preventing and detecting complications early. Nursing staff provides direct care to the patient, family, and community, applying principles such as early isolation, aggressive infection control, oxygen therapy, and fetal assessment. In addition, emotional support for the pregnant woman and her environment is vital to face isolation and concerns related to pregnancy and infection.Objective: To characterize nursing care in pregnant women diagnosed with COVID-19.Methods: A bibliographic review was conducted in databases such as PubMed, Google Scholar, and ResearchGate, using keywords including pregnancy, pregnant woman, COVID-19, nursing, and nursing care. Twenty articles were selected, from which relevant information was extracted.Discussion: Pregnancy is a unique immunological state that faces challenges to maintain tolerance to the fetus and defense against microbial agents. The care of these pregnant women requires multidisciplinary teams, maternal-fetal monitoring, and integral management. Nursing must offer humanized care, respiratory monitoring, vital signs control, oxygen therapy, and emotional support. Specialized training is key, especially in management. Promotion and prevention in the community, led by nursing, are essential to reduce risks and ensure safe pregnancies5.Conclusions: Nursing care in pregnant women con COVID-19 requires an integral intervention based on clinical protocols and humanized care. Constant monitoring, early detection of complications, protecting the mother-child binomial.